JURIDICAL REVIEW OF ABUSE OF CONDITION (MISBRUIK VAN OMSTANDIGHEDEN) AS REASON FOR CANCELLATION OF A DEBT AGREEMENT: This study aims to find out the reasons for the cancellation of the receivables debt agreement containing elements of Misbruik Van Omstandigheden and the legal consequences for the parties. In this study, normative juridical research methods were applied to examine laws and regulations, legal rules, and legal principles to answer the problem of misuse of the situation. The source - Brigitta Diffania; Wiwin Yulianingsih (JOSAR (Journal of Students Academic Research), 2022)
This study aims to find out the reasons for the cancellation of the receivables debt agreement containing elements of Misbruik Van Omstandigheden and the legal consequences for the parties. In this study, normative juridical research methods were applied to examine laws and regulations, legal rules, and legal principles to answer the problem of misuse of the situation. The source of the data is Judgment Number: 778/Rev.G/2017/PN. Jkt.Cells, laws and regulations, official documents, government regulations, and correlated literature. The results of the study concluded that the debt receivables agreement was made between the Plaintiff, Defendant, Co-Defendant I, Co-Defendant II and Co-Defendant III in Judgment Number: 778/Rev.G/2017/PN. Jkt.Sel about the misuse of circumstances in the debt receivables agreement that does not meet the subjective requirements is contained in Article 1320 of the Civil Code, so this agreement is considered an abuse of circumstances and it can be said that this agreement is null and void. As a result of the legal annulment of an agreement made because there is an abuse of the defective circumstances of the will in an agreement in which one of the parties to the agreement has a superior position, the agreement made and agreed upon becomes a null and void agreement with an element of abuse with economic superiority.